2014
DOI: 10.1111/joim.12189
|View full text |Cite
|
Sign up to set email alerts
|

Evolving biomarkers improve prediction of long‐term mortality in patients with stable coronary artery disease: the BIOVILCAD score

Abstract: Objective Algorithms to predict the future long‐term risk of patients with stable coronary artery disease (CAD) are rare. The VIenna and Ludwigshafen CAD (VILCAD) risk score was one of the first scores specifically tailored for this clinically important patient population. The aim of this study was to refine risk prediction in stable CAD creating a new prediction model encompassing various pathophysiological pathways. Therefore, we assessed the predictive power of 135 novel biomarkers for long‐term mortality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Past studies have disclosed the strong relationship between high serum levels of Cystatin C and the stable coronary artery disease [7], acute coronary syndrome (ACS), non-ST-elevation acute coronary syndrome (NSTEMI) [17] and ST elevated myocardial infarction (STEMI) [6]. The aim of current study was to investigate the relationship between the serum level of cystatin C and coronary artery lesions in CAD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have disclosed the strong relationship between high serum levels of Cystatin C and the stable coronary artery disease [7], acute coronary syndrome (ACS), non-ST-elevation acute coronary syndrome (NSTEMI) [17] and ST elevated myocardial infarction (STEMI) [6]. The aim of current study was to investigate the relationship between the serum level of cystatin C and coronary artery lesions in CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proposed Cystatin C as a novel biomarker for serum creatinine in the evaluation of early impaired renal dysfunction, predominantly to distinguish small drops in GFR [3,4]. Of interest, cystatin C has also been proposed as a useful biomarker for cardiovascular risk and associated with the mortality in diverse clinical scenarios [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Combination of multiple markers usually may enhance the risk assessment of CV disease. Kleber et al developed a new Vienna and Ludwigshafen CAD (VILCAD) biomarker risk score, which is a composite of age, haemoglobin A1c, LVEF, heart rate, NT-proBNP, sex, renin, 25-OH vitamin D, and cystatin C to predict the future long-term prognosis of patients with SCHD 27 . Compared to the original VILCAD score which did not include novel biomarkers, the new VILCAD biomarker risk score represents a valuable tool for risk prediction in patients with SCHD.…”
Section: Discussionmentioning
confidence: 99%
“…Kleber et al [32] suggested that BIO-VILCAD score including age, sex, left ventricular ejection fraction (EF), heart rate, N-terminal pro-brain natriuretic peptide, cystatin C, renin, 25OH-vitamin D3 and HbA1c, can be helpful in predicting the risk of long-term mortality in diabetics [32]. …”
Section: Timing Of Revascularizationmentioning
confidence: 99%